'Atomic' Music: Navigating experimental electronica and sound art through microsound. Issue 3 (13th November 2014) - Hofer, Sonya
<x content-type="archive" xml:space="preserve">Abstract</x> This paper looks at microsound – an emergent term, corresponding concept and associated genre of experimental electronica appearing in the late 1990s – which animates the idea of sound as material entity, and, as I will demonstrate, ultimately complicates and expands questions concerning disciplinary boundaries. The conceptualisation of sounds as having mass or as matter, particularly on an imagined 'atomic' level as is implicit in microsound, has had many historical antecedents, especially in the twentieth century. However, the comparison, representation and analogy of sound as an object of material composition is a peculiar metaphor as sound has no inherent material substance. At the meeting point of microsound, a wide spectrum of musicians and listeners across genres and subgenres has converged, along with a diverse range of technologies and approaches to those technologies. In what follows, an exploration of the inception and implications of microsound will offer one instructive path that helps elucidate the intertwined relationship between sound art and experimental electronica. Thus, this paper adds to the critical dialogue regarding these complex yet drastically under-theorised fields of creative activity by using microsound to articulate specific points of connection, commonality and divergence.